Peran Pembiayaan Syariah Dalam Mendorong Pertumbuhan Ekonomi Nasional : Pendekatan Error Correction Model (ECM) - Susetyo, Achmad Budi; Ningsih, Lailatul Berliana; Putri, Nasya Amelia; Fretika, Tatha Amelia; Triana, Devi; Amaliyah, Karimatul (CV. SINAR HOWUHOWU, 2025)
This study aims to analyze the impact of Islamic financing on Indonesia’s economic growth in both the short run and the long run using the Error Correction Model (ECM) approach. The study employs secondary time-series data obtained from the Central Bureau of Statistics (BPS), the Financial Services Authority (OJK), and Bank Indonesia (BI). Economic growth is used as the dependent variable, while Islamic financing serves as the main independent variable, with inflation, exchange rate, and Islamic interest rate included as control variables. The stationarity test results indicate that all variables are stationary at the first difference level, while the cointegration test confirms the existence of a long-run equilibrium relationship among the variables. The long-run estimation results reveal that Islamic financing, inflation, exchange rate, and Islamic interest rate have a significant effect on economic growth. However, in the short run, these variables do not exhibit a significant impact, and the adjustment mechanism toward long-run equilibrium does not operate effectively. These findings suggest that Islamic financing plays a more dominant role in promoting economic growth in the long run rather than in the short run. This study is expected to provide useful insights for policymakers and practitioners in the Islamic financial industry in formulating more effective and sustainable financing policies.